Diagnosis and treatment of gastrointestinal stromal tumor extending to prostate: A case report and literature review. Issue 46 (November 2016) - Xu, Huan; Liu, Chong; Chen, Yanbo; Gu, Meng; Cai, Zhikang; Chen, Qi; Wang, Zhong
Abstract: Rationale: Gastrointestinal stromal tumor (GIST) is the neoplasm of gastrointestinal tract. Patient concerns: The patient complained about the retention of urinary. Diagnoses: GIST. Interventions: radical prostatectomy and the imatinib therapy. Outcomes: No recurrence and metastasis have been found during a 14-month follow-up. Lessons: comprehensive treatment is necessary for the GIST treatment. Furthermore, we summarize a review of the literature of GIST occurring in the prostate gland treated by different methods and 4 kinds of rare diseases in prostate.